Outbreaks of Foodborne Disease Associated with Fruit and Vegetable Juices, 1922–2010 - Michelle D. Danyluk; Renée M. Goodrich-Schneider; Keith R. Schneider; Linda J. Harris; Randy W. Worobo (EDIS, 2012)
The FDA has recently mandated that all 100% fruit/vegetable juices sold wholesale be produced under a Hazard Analysis and Critical Control Point (HACCP) plan. As part of their HACCP plan, juice processors must identify and meet a target for reduction of the most resistant microorganism of public health significance that is likely to occur in the juice. This 7-page fact sheet aids juice processors in the identification of these “pertinent microorganisms,” and reviews the locations of juice preparations and severity of juice-associated outbreaks. Written by M. D. Danyluk, R. M. Goodrich-Schneider, K. R. Schneider, L. J. Harris, and R. W. Worobo, and published by the UF Department of Food Science and Human Nutrition, January 2012.